Monocyte‐derived dendritic cells from Crohn's disease patients exhibit decreased ability to activate T helper type 17 responses in memory cells. (July 2014) - Nieminen, J. K.; Sipponen, T.; Färkkilä, M.; Vaarala, O.
Summary An increased activation of interleukin (IL)‐17A‐producing immune cells is a well‐established feature of Crohn's disease (CD). Mechanisms that contribute to this aberrant immune activation are, however, less clear. Given that an enhanced induction of innate‐immunity associated cytokines IL‐6 and IL‐23, which promote IL‐17 immunity, is also clearly implicated in CD, we hypothesized that monocyte‐derived dendritic cells (moDCs) of CD patient origin would mount exaggerated IL‐17A responses in T cells. However, we found a significantly attenuated up‐regulation of the IL‐17A response in allogeneic T helper memory cells in the presence of culture media from lipopolysaccharide (LPS)‐stimulated moDCs of CD patients when compared with moDCs of control subjects (median fold‐increase in IL‐17A mRNA expression 1·09 versus 1·44, P = 0·038). This was accompanied by a lower expression of IL‐1β and IL‐6 transcripts in the LPS‐treated moDCs (median 9·55 versus 13·9 relative units, P = 0·042, and 2·66 versus 9·06 relative units, P = 0·049, respectively). In addition, the up‐regulation of autophagy‐related LC3 transcripts was decreased in moDCs of CD patients (median fold‐increase in mRNA expression 1·22 versus 1·52, P = 0·029). Our findings reveal similar immunological aberrancies in CD in the general population as reported in CD patients with mutated intracellular bacterial sensor NOD2, namely attenuated activation of innate cytokines and impaired autophagy, combined with a reduced capacity to up‐regulate the T helper type 17 (Th17) response. The results presented here emphasize a defective anti‐microbial response in the pathogenesis of CD. The increased mucosal Th1 and Th17 responses, which may contribute to the pathogenesis, could be the consequences of primary defects in the innate immunity.